Identification of Problems of Sweet Orange A Case Study from Pyuthan Municipality, Pyuthan - Adhikari, Aakash; G.C., Bigyan (International Journal of Applied Sciences and Biotechnology, 2022)
In view of suitable climatic condition in mid hill of Nepal, sweet orange is emerging as a new enterprise for farmers, for which the government of Nepal has also given priority to this crop. In the light of these facts, a case study was conducted in Pyuthan municipality of Pyuthan district to identify the problems related to sweet orange in Pyuthan municipality. All of the farmers had their own land for Sweet orange production. Majority of the respondents (80%) had the annual income below NRs. 20000. Farmers were able to increase their higher education, household expenses, health and savings from Sweet orange production. Transportation, irrigation, citrus greening disorder and green stinky bug were major problem in Sweet orange production in study area. Study suggested that concerned stakeholders should focus their program on quality seedling production, input use, and human resource management, and scientific orchard management, capacity development of farmers, insect pest management, scientific value chain management and post-harvest loss reduction for overall development of sweet orange industry in Pyuthan district. Int. J. Appl. Sci. Biotechnol. Vol 10(2): 134-139.